2014
DOI: 10.3892/br.2014.280
|View full text |Cite
|
Sign up to set email alerts
|

Associations of genetic variants in ADAM33 and TGF-β1 genes with childhood asthma risk

Abstract: Abstract. The aim of the present study was to explore the associations of genetic variants in the ADAM33 and TGF-β1 genes with the risk of childhood asthma. A total of 299 asthmatic children and 311 healthy controls were recruited in the hospital-based case-control study. The asthmatic subjects were further divided into mild and severe groups according to disease severity. Single-nucleotide polymorphisms (SNP) at ADAM33 V4, T2, S2 and T1, and TGF-β1 C-509T and T869C were selected and detected with PCR-RFLP. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The included studies were published between 2010 and 2020 and conducted in 11 countries: China, Indian, Egypt, Jordan, Poland, Mexico, Saudi Arabia, Colombia, Chile, Turkey, and Tunisia. A total of 18 polymorphisms in 7 genes were identified for data synthesis: IL-13 +2044G/A (rs20541), [ 10 – 15 ] IL-13 -1112C/T (rs1800925), [ 11 , 13 , 15 – 19 ] IL-13 +1923C/T (rs1295686), [ 20 – 22 ] IL-4 - 590C/T (rs2243250), [ 12 , 15 – 19 , 21 , 23 – 28 ] ADRB2 -46 G /A (rs1042713), [ 11 , 15 , 21 , 29 – 37 ] ADRB2 -79G/C (rs1042713), [ 29 , 31 35 , 38 ] ADAM33 F+1 (rs511898), [ 39 – 42 ] ADAM33 V4 (rs2787094), [ 39 , 40 , 43 – 45 ] ADAM33 S2 (rs528557), [ 15 , 39 , 41 , 44 , 45 ] ADAM33 T2 (rs2280090), [ 40 , 43 – 46 ] ADAM33 T1 (rs2280091), [ 40 , 41 , 44 , 45 ] ADAM33 ST+4 (rs44707), [ 39 , 47 , 48 ] ORMDL3 rs7216389, [ 49 – 52 ] VDR Apa I (rs7975232), [ 53 59 ] VDR Fok I (rs2228570), [ 53 55 , 57 , 58 , 60 , 61 ] VDR ...…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were published between 2010 and 2020 and conducted in 11 countries: China, Indian, Egypt, Jordan, Poland, Mexico, Saudi Arabia, Colombia, Chile, Turkey, and Tunisia. A total of 18 polymorphisms in 7 genes were identified for data synthesis: IL-13 +2044G/A (rs20541), [ 10 – 15 ] IL-13 -1112C/T (rs1800925), [ 11 , 13 , 15 – 19 ] IL-13 +1923C/T (rs1295686), [ 20 – 22 ] IL-4 - 590C/T (rs2243250), [ 12 , 15 – 19 , 21 , 23 – 28 ] ADRB2 -46 G /A (rs1042713), [ 11 , 15 , 21 , 29 – 37 ] ADRB2 -79G/C (rs1042713), [ 29 , 31 35 , 38 ] ADAM33 F+1 (rs511898), [ 39 – 42 ] ADAM33 V4 (rs2787094), [ 39 , 40 , 43 – 45 ] ADAM33 S2 (rs528557), [ 15 , 39 , 41 , 44 , 45 ] ADAM33 T2 (rs2280090), [ 40 , 43 – 46 ] ADAM33 T1 (rs2280091), [ 40 , 41 , 44 , 45 ] ADAM33 ST+4 (rs44707), [ 39 , 47 , 48 ] ORMDL3 rs7216389, [ 49 – 52 ] VDR Apa I (rs7975232), [ 53 59 ] VDR Fok I (rs2228570), [ 53 55 , 57 , 58 , 60 , 61 ] VDR ...…”
Section: Resultsmentioning
confidence: 99%
“…32 rs1800469 is a functional genetic variant of TGF-β1 that has been studied as a potent asthma susceptible variant in many populations. 23,24,33,34 rs2241715 is located in the intronic region of TGF-β1 that has been evaluated as a potential risk factor for asthma in various populations. 21,25,22 Current study is the first effort to evaluate the association pattern of these SNPs with asthma in Pakistani population.…”
Section: Discussionmentioning
confidence: 99%
“…24,33 In contrast to our findings, some studies have shown the significant association of SNP rs1800469 with asthma. 23,34 These dissimilarities in results might be owing to various factors like ethnicity, geographical locations, life style and environmental factors. Sample size is another important factor that can affect the outcome of case-control based population studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies were published between 2010 and 2020 and were conducted in ten countries: China, Indian, Egypt, Jordan, Poland, Mexico, Saudi Arabia, Colombia, Turkey and Tunisia. A total of 18 polymorphisms in 7 genes were identi ed for data synthesis: IL-13 + 2044G/A (rs20541) 10-14 , IL-13 -1112C/T(rs1800925) 11,13,15−18 , IL-13 + 1923C/T (rs1295686) 19,20 , IL-4 -590C/T (rs2243250) 12,15-18,20−25 , ADRB2 -46 G /A(rs1042713) 11,20,26−31 , ADRB2 -79G/C (rs1042713) 26,28−32 , ADAM33 F + 1(rs511898) 33-36 , ADAM33 V4 (rs2787094) 33,34,37−39 , ADAM33 S2(rs528557) 33,35,38,39 , ADAM33 T2 (rs2280090) 34,37−39 , ADAM33 T1(rs2280091) 34,35,38,39 , ADAM33 ST + 4 (rs44707) 33,40,41 , ORMDL3 rs7216389 42-44 , VDR Apa (rs7975232) [45][46][47][48][49] , VDR Fok (rs2228570) 45-47,49−51 ,VDR Bsm (rs1544410) [46][47][48][49]51 , VDR Taq (rs731236) [45][46][47]49 , and CTLA-4 + 49 G/A (rs231775) [52][53][54] . The detailed characteristics of included studies are given in Table 1.…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%